Ubiquitous computing: a learning system solution in the era of industry 4.0 - Wildan Toyib; Delvis Agusman; Hari Ramza (Universitas Ahmad Dahlan, 2020)
Ubiquitous computing, which was initially advocated by Mark Weiser has become one of the keywords to express a vision of the near future of computing systems. The